2015
DOI: 10.1016/j.ecoleng.2015.04.087
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a semi-batch vertical-flow wetland for onsite residential graywater treatment

Abstract: Available online xxx Keywords: Graywater treatment Vertical flow wetland Nonpotable water reuse Biofilm Semi-batch A B S T R A C TThe technical feasibility of graywater treatment, via a semi-batch vertical flow wetland (SB-VFW), was evaluated at a single family home for aboveground water reuse. Graywater treatment was achieved to a quality level that was well within the regulatory compliance limits (e.g., with respect to biochemical oxygen demand (BOD), total suspended solids (TSS) and turbidity) for above gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…One of the advantages of using OFP in CWs is the significant reduction of nutrient contamination (20-35%; Figure 2) comparing when CWs unplanted, representing an economical and sustainable alternative to decentralization practices; CWs are less expensive than commercial systems and are easier to build and operate [16,72]. Furthermore, by using plants with commercial value, the resources invested in the design, construction and maintenance of the system can be recovered in the profits of retail sales, without impeding the removal of pollutants of the system.…”
Section: Advantages Of Using Ornamental Plants In Cwsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the advantages of using OFP in CWs is the significant reduction of nutrient contamination (20-35%; Figure 2) comparing when CWs unplanted, representing an economical and sustainable alternative to decentralization practices; CWs are less expensive than commercial systems and are easier to build and operate [16,72]. Furthermore, by using plants with commercial value, the resources invested in the design, construction and maintenance of the system can be recovered in the profits of retail sales, without impeding the removal of pollutants of the system.…”
Section: Advantages Of Using Ornamental Plants In Cwsmentioning
confidence: 99%
“…The type of vegetation used are plants from natural wetlands, including Cyperus papyrus, Phragmites australis, Typha and Scirpus spp., which have been evaluated for their positive effects on treatment efficiency for nutrient and organic compounds around the globe [8,9,11]. In Americas, such species are typical in CWs, and are found mainly in the United States, where the technology has been used extensively and is implemented in different rural and urban zones [12][13][14][15][16]. In recent studies (15 years ago), the goal of CW studies involved an investigation into the use of herbaceous perennial ornamental plants in CWs, including the use of species with different colored flowers to make the systems more esthetic, and therefore making it more probable for adoption and replication.…”
Section: Introductionmentioning
confidence: 99%
“…Wu, Fan, Zhang, Ngo, Guo, Hu et al (2015) revealed that intermittent aeration was an appropriate operation strategy for enhancing organic pollutants and nitrogen removal in VFCW. Another study (Yu, Bill et al, 2015) showed a semi-batch VFCW could reduce the pollutants (BOD, TSS, and turbidity) level to below regulatory limits, thus the semi-batch VFCW design was feasible for onsite residential greywater treatment. Osmanaj et al (2015) discussed the potential of CWs for wastewater treatment in rural areas in Kosovo with combination of 1 st stage VFCW and 2 nd stage HFCW.…”
Section: Onsite Treatmentmentioning
confidence: 99%
“…(Friedler et al 2005), but impedes the adoption of onsite graywater treatment in lowdensity residential housing such as single-family homes. More recent work by Yu et al (2015) showed that relatively short breakeven periods are achievable using a wetland treatment system for above-ground nonpotable graywater recycling in a single-family home. Even shorter payback periods and broader economic implications of onsite graywater reuse may be possible in cities in arid regions that are facing water scarcity and have limited capability for reusing centralized recycled water due to the lack of a distribution system.…”
mentioning
confidence: 99%